Photon structure functions at small x in holographic QCD - Akira Watanabe (Physics Letters B, 2015)
We investigate the photon structure functions at small Bjorken variable x in the framework of the holographic QCD, assuming dominance of the Pomeron exchange. The quasi-real photon structure functions are expressed as convolution of the Brower–Polchinski–Strassler–Tan (BPST) Pomeron kernel and the known wave functions of the U(1) vector field in the five-dimensional AdS space, in which the involved parameters in the BPST kernel have been fixed in previous studies of the nucleon structure functions. The predicted photon structure functions, as confronted with data, provide a clean test of the BPST kernel. The agreement between theoretical predictions and data is demonstrated, which supports applications of holographic QCD to hadronic processes in the nonperturbative region. Our results are also consistent with those derived from the parton distribution functions of the photon proposed by Glück, Reya, and Schienbein, implying realization of the vector meson dominance in the present model setup.